How a Consumer Search for Multiple Information Sources to get Price Satisfaction: the Mediating Role of Online Trust. - Kaur, Amandeep (Gyan Management Journal, 2020)
The mediating role of online trust in enhancing calculative commitment and customer loyalty through online relationship marketing activities (engagement and interactivity). However, signals communicated through interactivity online is of great benefit to the banks in influencing customers' online trust, also as their calculative commitment and loyalty. Further, though, website and email emerged because the most predominant technologies utilized in online relationship marketing (ORM), customers also expect banks to interact with them through social media, which has the potential to enhance upon the present levels of CRM activities. When making important purchase decisions, consumers often consult multiple information sources. How consumers allocate their search time across offline and Internet sources using survey data from new automobile purchases. How time spent on Internet sources interrelates with time spent on offline sources, like car dealerships, and the other way around . Furthermore, whether longer search times imply higher price satisfaction as an outcome of search. (1) Specific website types can complement or substitute for offline information sources sand for each other and (2) Longer search times result in increased price satisfaction but only on specific information sources
Keywords: Corporate Identity; Corporate Image; Corporate Reputation; Social Identity; Customer Trust; Customer Loyalty